Qualitative attributes and postharvest conservation of green ears of maize grown on different cover crops in organic no-till system - Favarato, Luiz Fernando; Souza, Jacimar Luis de; Galvão, João Carlos Cardoso; Souza, Caetano Marciano de; Balbino, José Mauro de Souza; Guarçoni, Rogério Carvalho (Revista Ceres, 2016)
Postharvest quality of sweet maize varies depending on the type of seed, soil, quality of fertilizer, climatic conditions, and stage of maturation. This study aimed to evaluate the post-harvest quality and shelf life of green ears of maize grown on three soil covers in organic no-till sytem. The study was conducted in the municipality of Domingos Martins, ES (20° 22’16.91" S and 41° 03' 41.83" W). The experiment was arranged in a randomized block design with six replications and five treatments, consisting of three cover crops in organic no-till system: black-oat straw, white lupin, oat/lupin intercrop and two systems, organic and conventional, without straw. Maize double hybrid AG-1051 was sown in a spacing of 1.00 x 0.20 m. The variables evaluated included relative percentage of grain, straw and cob, pH, titratable acidity, soluble solids, grain moisture and shelf life. The use of different straws in the organic no-till system does not influence the postharvest quality of green ears. Ears packed in polystyrene trays with plastic film are suitable for marketing until the fifth day of storage at room temperature.